Gasoline Prices : Policies and Proposals. (U.S. Congressional Research., 2005)
Examines factors responsible for increases in gasoline prices and proposals to address problems in the oil and gasoline markets. Covers policy options, status of legislation, and major oil-related issues, including oil and gas exploration in the Arctic National Wildlife Refuge, corporate average fuel economy standards, outer continental shelf leasing, refinery revitalization, and price gouging following Hurricane Katrina. Also reviews relevant legislation in the 109th Congress.